Planning Study of Wastewater Treatment Plant Communal Settlement Perumnas III Waena Yabansai Village Heram District Jayapura City - Alberth Einstein Stevann Abrauw; Alfred Benjamin Alfons (Postgraduate, University of Mataram, 2023)
The effect of population growth in the residential area of Perumnas III Waena which is lack of planning has an impact on groundwater pollution caused by domestic waste water which affects the quality of dug well water. Household domestic waste water that comes from the combination of cleaning activities, namely waste from kitchen, bathroom, toilet, and laundry with the composition of liquid waste containing organic materials and mineral compounds from food scraps, urine and soap. The objective of this research is to make plans for Waste Water Treatment (IPAL) Communal Plants at Perumnas III Waena which can serve waste water treatment in these settlements. The data analysis method used is the calculation of the population, analysis of water discharge, determination of water discharge and technical planning of Waste Water Treatment (IPAL) Communal Plants. The results show that the discharge of the entire settlement is 0,04780 m3 / second, the distribution planning system in the residential area III Waena is designed with a Small Bore Sawer system equipped with an inceptor tank at the end of the house channel, a communal wastewater treatment plant (IPAL) with an Off-Site system with Aerobic Anaeorob Reactor Biofilter technology